An analysis of Investment Pattern of Salaried Employees - A Case Study of Visakhapatnam - Purnima, Mrs. D.; Lalitha, Dr. N. (The journal of contemporary issues in business and government, 2021)
In General sense, the term investment is an type of activity that is being engaged in by the people who have to do savings i.e. investments are made from their savings, or in other words it is the people invest their savings. At present a variety of different investment options are available to the investors that are bank, Gold, Real estate, post services, mutual funds & so on much more. Investors are always investing their money with the different types of purpose and objectives such as profit, security, appreciation, Income stability. Researcher in this study has studied the different types and avenues of investments available and the factors that are required to be considered while selecting the investment with the sample size of 100 salaried employees by conducting the survey in Visakhapatnam City, India. The study identifies the preferred investment avenues among individual investors using their own self-assessment test for the purpose. The analysis established that that salaried employees are considering the safety as well as good return on investment as top priority before investment . Respondents are much more aware about the different investment avenues available in India except female investors.